STUDI EKSPLORATIF KREATIVITAS YANG DILAKUKAN GURU PADA PROSES PEMBELAJARAN DIMASA PANDEMI COVID-19 - Haris Kurniawan; Eva Susanti (STKIP Andi Matappa, 2020)
This study aims to search for and find information and discuss what strategies are undertaken by teachers in the process of encouraging learning, which courage learning is an Indonesian government policy on education in a framework supported by the Covid-19 pandemic. This research was conducted by exploring case studies using qualitative data. Respondents in this study were randomly distributed to school teachers in Palembang. Consisting of 44 respondents spread across 10 city districts in the province. By using questionnaire and interview data compiled based on literature review. 100% of respondents adapted the system of change with 50% of respondents learning by creating and innovating integrating bold learning media according to the needs and abilities they offer While adjusting to internet network limitations or learning limitations.